3D numerical simulation of the gas detonation forming of aluminum tubes considering fluid-structure interaction and chemical kinetic model. (April 2021) - Rokhy, Hamid; Mostofi, Tohid Mirzababaie
Abstract: The present study deals with the numerical simulation of the dynamic response of the pure aluminum AA1050 tube under internal gas mixture detonation loading. This practical topic involves structural large plastic deformation, fluid motion, and chemical reaction, and detonation wave/structure interaction. Therefore, the Fluid-Structure Interaction (FSI) with finite-rate chemistry in compressible Conservation Element/Solution Element (CESE) solver with the Immersed Boundary Method (IBM) was used to model the real situation of the whole forming process. The numerical model was verified with existing experimental data for aluminum tubes under internal gas detonation of H2 +O2 in terms of the pressure-time history and deformation pattern. Moreover, the simulation results were also compared to those numerical ones in the open literature. It is found that the current numerical modelling approach reproduces the experimental observations very well, and it has a more accurate prediction capability in comparison to the reported study. Hence, the present numerical approach can be used for the design of pressure vessels and piping systems subjected to internal gas detonation loading and also further studies on hazard analysis of pipeline explosion accidents. Moreover, the effect of ignition point location, double ignition points, initial pressure, and repeated loading on the response was investigated. The results show that an experimental setup with double ignition points gives a uniform distribution for plastic deformation in the longitudinal direction of the tube while the ignition point is located at a distance of 1/6 length of the tube from both ends. Furthermore, the double gas detonation loading at the low initial pressure of 0.85 MPa gives the same result obtained for single loading at the moderate initial pressure of 1.2 MPa. Highlights: The dynamic response of pure aluminum tubes under internal gas mixture detonation loading was investigated. FSI with finite-rate chemistry in the CESE solver with the IBM method was used for numerical simulations. The numerical model was verified with existing experimental data for aluminum tubes under internal gas detonation of H2 +O2 . The effect of ignition point location, double ignition points, initial pressure, and repeated loading on the response was further studied.